Analysis of the Impact of Technology Use on Multimodality and Activity Travel Characteristics. Issue 1 (2017) - Astroza, Sebastian; Garikapati, Venu M.; Bhat, Chandra R.; Pendyala, Ram M.; Lavieri, Patrícia S.; Dias, Felipe F.
Smartphone ownership and use are becoming increasingly prevalent around the world. However, little is known about the impacts of this technology on activity travel choices. The objective of this study was to determine the extent to which smartphone ownership and use influence activity travel demand, after controlling for other lifestyle and demographic attributes. The impacts of smartphone ownership and use on multiple travel dimensions were examined through the specification and estimation of a joint model system that explicitly accounts for self-selection effects arising from lifestyle preferences (such as green lifestyle propensity and technology savviness). Specifically, the impacts of smartphone ownership and use on the following choice dimensions were estimated: ( a ) use of multiple modes of transportation, ( b ) pursuit of complex trip chains with a large number of intermediate stops, ( c ) engagement in tours that have a recreational activity, and ( d ) participation in joint tours that involve an accompanying person. Travel survey data from the 2014–2015 Puget Sound (Washington) Regional Travel Study were used. The results show substantial and statistically significant effects of smartphone ownership and use on activity travel patterns, even after controlling for lifestyle preferences. Smartphone ownership and use were found to increase the likelihood of using multiple modes of transportation and participating in complex tours, joint tours, and recreational tours.